High-water-absorption konjac hydrogel polymer and preparation method thereof

By acetylated konjac glucomanan and modified chitosan, combined with nanocellulose and calcium chloride ion cross-linking, using interface induction method and freeze-drying technology, a highly absorbent konjac hydrogel polymer was prepared, which solved the problem. The problem of insufficient stability and mechanical strength of konjac hydrogel in an acidic environment has achieved high water absorption and slow expansion.

CN119144054AActive Publication Date: 2024-12-17SHANGHAI XUQING MEDICAL TECH CO LTD

Patent Information

Application Number
CN202411630785.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2024-12-17
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

Konjac hydrogel has poor physical and chemical stability under different environmental conditions, especially in acidic environments, which affects its expansion and water absorption ability. Its mechanical strength is insufficient, making it difficult to maintain stability in a complex digestive system.

Method used

Through acetylated konjac glucomanan and modified chitosan, nanocellulose and calcium chloride ion cross-linking were introduced, combined with interface induction method and freeze-drying technology, a highly absorbent konjac hydrogel polymer was prepared to enhance its Stability and mechanical strength and surface properties are adjusted by beeswax and MCT medium chain triglycerides.

Benefits of technology

It significantly improves the stability and mechanical strength of konjac hydrogel, delays the speed of water entry, enhances acid resistance in acidic environments, achieves slow expansion and high water absorption performance, and improves residence time and drugs in the digestive tract. Applicability of the preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144054A_ABST
    Figure CN119144054A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional polymers, and particularly relates to a high-water-absorption konjac hydrogel polymer and a preparation method thereof. The konjac hydrogel polymer is prepared from the following raw materials in parts by weight: 30 to 40 parts of acetylated konjac glucomannan, 10 to 15 parts of modified chitosan, 5 to 8 parts of calcium chloride solution, 1 to 3 parts of acetic acid solution, 3 to 5 parts of nano cellulose, 2 to 5 parts of beewax, 10 to 15 parts of MCT medium chain triglyceride and 1 to 3 parts of emulsifier. According to the invention, through acetylation modified konjac glucomannan, hydrophilicity is reduced, water absorption is delayed, and stability of an acidic environment is improved; the mechanical strength is enhanced through crosslinking, the hydrophobicity is improved through chitosan modification, and the mechanical strength and toughness are improved through nanocellulose; the surface is coated with a beeswax and MCT mixture to adjust the surface property and delay water absorption; an interface induction method is combined with a freeze-drying technology to generate a porous structure, so that the water absorption efficiency and the structural integrity are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional polymers, and in particular relates to a highly water-absorbent konjac hydrogel polymer and a preparation method thereof. Background Art

[0002] Konjac hydrogel is a highly absorbent material based on konjac glucomannan. Due to its excellent water absorption and swelling properties, it has been widely used in many fields, especially in food, medicine and health. Konjac glucomannan is a natural non-starch polysaccharide, whose molecular structure is composed of glucose and mannose, and is a kind of dietary fiber. This fiber can absorb a large amount of water and form a viscous gel-like substance when it comes into contact with water, and its water absorption capacity can reach more than 50 times its own volume. This property makes konjac hydrogel an ideal candidate ingredient for weight management and intestinal health products, because it can expand rapidly in the gastrointestinal tract, increase satiety, and slow down gastric emptying, which helps to reduce food intake. In addition, the viscous properties of konjac glucomannan help promote intestinal peristalsis, improve intestinal function, reduce the incidence of constipation, and regulate the balance of intestinal flora. However, although konjac hydrogel exhibits significant swelling and water absorption capacity, it still faces some technical challenges in practical applications, especially the physical and chemical stability issues under different environmental conditions. The viscosity of konjac hydrogel is highly sensitive to external factors such as pH value, ionic strength and temperature of solution. Especially in acidic environment (such as gastric acid), the viscosity of konjac glucomannan tends to significantly decrease, thereby weakening its expansibility and water absorption capacity, and this viscosity change not only affects the physical stability of konjac hydrogel, but also may reduce its actual efficacy in vivo. Although konjac hydrogel has good expansion capacity, its mechanical strength is relatively weak. Under the mechanical force or external pressure of the gastrointestinal tract, the gel structure is easily broken or deformed, causing it to be difficult to maintain stability in a complex digestive system environment, which limits its application in the fields of food and pharmaceutical preparations. Therefore, based on the above problems, it is extremely necessary to develop a konjac hydrogel polymer with high water absorption, high stability and slow expansion. Summary of the invention

[0003] In view of the defects of the prior art, the object of the present invention is to provide a highly water-absorbent konjac hydrogel polymer and a preparation method thereof.

[0004] The technical effect of the present invention is achieved by the following technical scheme: a highly water-absorbent konjac hydrogel polymer, which comprises the following raw materials in parts by weight: 30 to 40 parts of acetylated konjac glucomannan, 10 to 15 parts of modified chitosan, 5 to 8 parts of calcium chloride solution, 1 to 3 parts of acetic acid solution, 3 to 5 parts of nanocellulose, 2 to 5 parts of beeswax, 10 to 15 parts of MCT medium chain triglycerides and 1 to 3 parts of emulsifier.

[0005] Preferably, the emulsifier is any one of lecithin, Tween-80 and glyceryl monostearate.

[0006] Preferably, the concentration of the calcium chloride solution is 0.2-0.5M.

[0007] Preferably, the concentration of the acetic acid solution is 0.1-0.2M.

[0008] Preferably, the specific preparation steps of the acetylated konjac glucomannan are as follows: A1: adding konjac glucomannan to distilled water, stirring and dissolving uniformly to obtain a 5-10wt% konjac glucomannan solution; cooling the konjac glucomannan solution to 0-5°C, then adding sodium citrate to adjust the pH to 6.5-7, slowly adding acetic anhydride dropwise under continuous stirring, stirring and reacting for 2-3h, after the reaction is completed, adding 3-4 times the volume of the solution ethanol to terminate the reaction, centrifuging at 6000rpm for 10min, washing with distilled water until neutral, and vacuum drying at 50-60°C to constant weight to obtain acetylated konjac glucomannan.

[0009] Preferably, in step A1, the amount of acetic anhydride used is 1-2% of the volume of the konjac glucomannan solution.

[0010] Preferably, the specific preparation steps of the modified chitosan are as follows: B1: Dissolve chitosan in 0.1M acetic acid aqueous solution, stir and dissolve evenly to obtain a chitosan solution with a concentration of 1-2wt%; dissolve hexadecyltrimethylammonium bromide in dimethyl sulfoxide solvent, heat to 50°C in a water bath, stir and dissolve evenly to obtain a hexadecyltrimethylammonium bromide solution; B2: Slowly add the hexadecyltrimethylammonium bromide solution prepared in step B1 to the chitosan solution, heat it in a water bath to 50-60°C, control the pH to 4-5, react for 3-6 hours, pour the reaction solution into an ethanol solution of 3-4 times the total volume of the solution three times, centrifuge, filter, wash with ethanol three times, and vacuum dry at 60°C to constant weight to obtain modified chitosan.

[0011] Preferably, in step B1, the ratio of the amount of hexadecyltrimethylammonium bromide to the amount of dimethyl sulfoxide solvent is 0.15-0.3 g:1 mL; Preferably, in step B2, the volume ratio of the hexadecyltrimethylammonium bromide solution to the chitosan solution is 0.6 to 1:1.

[0012] Preferably, another aspect of the present invention is to provide a method for preparing a highly water-absorbent konjac hydrogel polymer, wherein the specific preparation steps are as follows: S1: dissolving acetylated konjac glucomannan in distilled water, stirring and dissolving uniformly, obtaining a 1-3wt% acetylated konjac glucomannan solution; dissolving modified chitosan in acetic acid solution, stirring and dissolving uniformly, obtaining a chitosan solution; adding nanocellulose to distilled water, dispersing uniformly by ultrasonic treatment, obtaining a 1-2wt% nanocellulose suspension; S2: slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH to 5.5-6.5 during the process, stirring continuously for 30-60 minutes, gradually adding the nanocellulose suspension prepared in step S1, stirring continuously for 30-50 minutes, gradually adding the calcium chloride solution, stirring continuously for 30-60 minutes, and obtaining a gel solution; S3: Add three quarters of MCT medium chain triglyceride by weight to a beaker, add an emulsifier, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 2000-3000 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, emulsify for 15-30 minutes, and stand for 30 minutes after emulsification to obtain an emulsion; S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel particles; S5: beeswax and one quarter of the weight of MCT medium chain triglyceride are mixed, and the mixture is heated in a water bath to 70°C for complete dissolution to obtain a coating liquid. The gel particles prepared in step S3 are preheated to 40°C, and then added to the coating liquid. After stirring for 1 to 2 minutes, the gel particles are separated by a sieve, and the mixture is immediately cooled and solidified at 4°C to obtain a konjac hydrogel polymer.

[0013] Preferably, in step S2, the nanocellulose suspension is added in three batches; the calcium chloride solution is added in four batches; Preferably, the specific operation of the freeze-drying treatment in step S4 is as follows: set the temperature of the freeze dryer to -50°C and the vacuum degree to 0.1 mbar, dry the pre-frozen gel at -50°C for 24 hours, and then increase the temperature to 20°C at a rate of 1°C / min and dry for 6 hours.

[0014] The beneficial effects of the present invention are as follows: The present invention carries out acetylation modification to konjac glucomannan, effectively reduces its hydrophilicity, delays the speed of water entering gel, and improves the stability of gel under acidic and neutral conditions simultaneously, the introduction of acetylated groups can also produce hydrophobic interaction with the long-chain alkyl of hexadecyl modified chitosan, strengthens the stability and mechanical strength of gel network, in addition, acetylation treatment gives hydrogel certain acid resistance, enables it to maintain structural integrity in gastric acid environment, thereby strengthens its application effect in complex digestive system. Multivalent metal ion crosslinking (calcium ion) further improves the mechanical strength of hydrogel by forming a stable crosslinking network with konjac glucomannan, metal ion crosslinking not only enhances the structural stability of gel, but also can regulate the hydrophilicity of gel, delays the initial water absorption rate, and gradually improves the water absorption performance after water molecules penetrate into the crosslinking network simultaneously, showing the high water absorption of progressive acceleration. The dual structure constructed jointly by acetylation modification and metal ion crosslinking can not only slow down the initial water absorption rate, but also provide sufficient adsorption sites for subsequent water diffusion, so that hydrogel keeps good mechanical strength in water absorption process. The hexadecyl long-chain modification of chitosan can form a tighter molecular arrangement in the gel network through hydrophobic interaction, making the gel more stable and less prone to rupture or instability during water absorption and swelling. Hexadecyl-modified chitosan can also play a synergistic role in the interface induction method. Due to the introduction of hydrophobicity, a more stable phase separation structure is formed at the water-oil interface, promoting the formation of pores.

[0015] The present invention significantly improves the mechanical strength and toughness of the hydrogel by introducing nanocellulose. As a physical reinforcing material, nanocellulose interacts with the cross-linked network of konjac glucomannan to form a stable supporting structure, so that the hydrogel is not easy to break or become unstable during the water absorption and swelling process. At the same time, the high specific surface area of ​​nanocellulose helps to enhance the water absorption performance in the later stage. Through its hydrophilicity and nanoscale structure, nanocellulose promotes the diffusion of water inside the gel while improving the structural strength, thereby improving the high water absorption capacity of the hydrogel. A layer of a mixed coating liquid of natural edible lipophilic substances beeswax and MCT medium-chain triglycerides is coated on the surface of the hydrogel to further adjust the surface properties of the hydrogel. The coating has a certain hydrophobicity, which can delay the entry of water from the outside into the gel, and further achieve the effect of slow water absorption; in addition, the plant wax has good biocompatibility and safety, and can also protect the structural integrity of the hydrogel in the digestive tract, prevent it from being degraded prematurely, and prolong its residence time in the digestive tract.

[0016] The present invention utilizes the interfacial induction method combined with freeze-drying technology to generate a porous structure inside the hydrogel, significantly improving its specific surface area and water transfer efficiency. The introduction of the porous structure effectively delays the initial water absorption rate, and based on the need for water, it gradually enters the gel through these pores, thereby achieving the effect of sustained-release water absorption; at the same time, freeze-drying technology forms a stable and uniform microporous network, so that the hydrogel can expand rapidly after absorbing a certain amount of water, increase the water absorption capacity, and maintain the structural integrity of the gel. Through the above synergistic effect, not only the residence time of the hydrogel in the digestive tract is extended, but also its applicability in pharmaceutical preparations and dietary supplements is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 It is a deionized water absorption test graph of the konjac hydrogel polymer prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 2 It is a test graph of simulated gastric fluid water absorption of konjac hydrogel polymers prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 3 It is a test graph of simulated intestinal fluid water absorption of konjac hydrogel polymers prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 4 It is a graph showing the compressive strength test results of the konjac hydrogel polymers prepared in Example 2 of the present invention and Comparative Examples 1 to 4; Figure 5 The biocompatibility test of the konjac hydrogel polymer prepared in Examples 1 to 3 of the present invention; Figure 6 It is the SEM scanning spectrum of the konjac hydrogel polymer prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0019] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.

[0020] Example 1: A highly absorbent konjac hydrogel polymer, comprising the following raw materials in parts by weight: 30 parts of acetylated konjac glucomannan, 10 parts of modified chitosan, 5 parts of calcium chloride solution, 1 part of acetic acid solution, 3 parts of nanocellulose, 2 parts of beeswax, 10 parts of MCT medium chain triglycerides and 1 part of emulsifier.

[0021] Preparation of acetylated konjac glucomannan: A1: Add konjac glucomannan to distilled water, stir and dissolve evenly to obtain a 5wt% konjac glucomannan solution; cool 200mL of the konjac glucomannan solution to 5°C, then add sodium citrate to adjust the pH to 7, slowly add 2mL of acetic anhydride dropwise under continuous stirring, stir and react for 2h, after the reaction is completed, add 600mL of ethanol to terminate the reaction, centrifuge at 6000rpm for 10min, wash with distilled water until neutral, and vacuum dry at 50°C to constant weight to obtain acetylated konjac glucomannan; Preparation of modified chitosan: B1: Dissolve chitosan in 0.1M acetic acid aqueous solution, stir and dissolve evenly to obtain a chitosan solution with a concentration of 1wt%; dissolve 75mg of hexadecyltrimethylammonium bromide in 500mL of dimethyl sulfoxide solvent, heat to 50°C in a water bath, stir and dissolve evenly to obtain a hexadecyltrimethylammonium bromide solution; B2: Slowly drop 500 mL of the hexadecyltrimethylammonium bromide solution prepared in step B1 into 500 mL of the chitosan solution, heat to 50°C in a water bath, control the pH to 4, react for 6 hours, pour the reaction solution into 3000 mL of ethanol solution three times, centrifuge, filter, wash with ethanol three times, and vacuum dry at 60°C to constant weight to obtain modified chitosan; Preparation of Konjac Hydrogel Polymer: S1: dissolving acetylated konjac glucomannan in distilled water, stirring and dissolving uniformly to obtain a 1wt% acetylated konjac glucomannan solution; dissolving modified chitosan in 0.1M acetic acid solution, stirring and dissolving uniformly to obtain a chitosan solution; adding nanocellulose to distilled water, dispersing uniformly by ultrasonic treatment, and obtaining a 1wt% nanocellulose suspension; S2: slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH to 5.5 during the process, stirring continuously for 30 min, adding the nanocellulose suspension prepared in step S1 in three batches, stirring continuously for 30 min, adding 0.2 M calcium chloride solution in four batches, stirring continuously for 30 min, to obtain a gel solution; S3: Add three quarters of MCT medium chain triglyceride in a beaker, add lecithin, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 2000 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, emulsify for 30 minutes, and stand for 30 minutes after emulsification to obtain an emulsion; S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel. Set the temperature of the freeze dryer to -50°C and the vacuum degree to 0.1 mbar. Dry the pre-frozen gel at -50°C for 24 hours, and then heat it to 20°C at a rate of 1°C / min and dry it for 6 hours to obtain gel particles. S5: Mix beeswax and one quarter of the weight of MCT medium-chain triglycerides, heat in a water bath to 70°C to completely dissolve, and obtain a coating liquid. Preheat the gel particles prepared in step S3 to 40°C, and then add them to the coating liquid. After stirring for 1 minute, separate the gel particles with a sieve, and immediately cool and solidify at 4°C to obtain a konjac hydrogel polymer.

[0022] Example 2: A highly absorbent konjac hydrogel polymer, comprising the following raw materials in parts by weight: 40 parts of acetylated konjac glucomannan, 15 parts of modified chitosan, 8 parts of calcium chloride solution, 3 parts of acetic acid solution, 5 parts of nanocellulose, 5 parts of beeswax, 15 parts of MCT medium chain triglycerides and 3 parts of emulsifier.

[0023] Preparation of acetylated konjac glucomannan: A1: Add konjac glucomannan to distilled water, stir and dissolve evenly to obtain a 10wt% konjac glucomannan solution; cool 200mL of the konjac glucomannan solution to 0°C, then add sodium citrate to adjust the pH to 6.5, slowly add 4mL of acetic anhydride dropwise under continuous stirring, stir and react for 3h, after the reaction is completed, add 800mL of ethanol to terminate the reaction, centrifuge at 6000rpm for 10min, wash with distilled water until neutral, and vacuum dry at 60°C to constant weight to obtain acetylated konjac glucomannan; Preparation of modified chitosan: B1: Dissolve chitosan in 0.1M acetic acid aqueous solution, stir and dissolve evenly to obtain a chitosan solution with a concentration of 2wt%; dissolve 150mg of hexadecyltrimethylammonium bromide in 500mL of dimethyl sulfoxide solvent, heat to 50°C in a water bath, stir and dissolve evenly to obtain a hexadecyltrimethylammonium bromide solution; B2: Slowly drop 300 mL of the hexadecyltrimethylammonium bromide solution prepared in step B1 into 500 mL of the chitosan solution, heat to 60°C in a water bath, control the pH to 5, react for 5 hours, pour the reaction solution into 3200 mL of ethanol solution three times, centrifuge, filter, wash with ethanol three times, and vacuum dry at 60°C to constant weight to obtain modified chitosan; Preparation of Konjac Hydrogel Polymer: S1: dissolving acetylated konjac glucomannan in distilled water, stirring and dissolving uniformly, obtaining a 3wt% acetylated konjac glucomannan solution; dissolving modified chitosan in 0.2M acetic acid solution, stirring and dissolving uniformly, obtaining a chitosan solution; adding nanocellulose to distilled water, dispersing uniformly by ultrasonic treatment, obtaining a 2wt% nanocellulose suspension; S2: slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH to 6.5 during the process, stirring continuously for 60 min, adding the nanocellulose suspension prepared in step S1 in three batches, stirring continuously for 50 min, adding 0.5 M calcium chloride solution in four batches, stirring continuously for 60 min, to obtain a gel solution; S3: Add three quarters of MCT medium chain triglyceride by weight to a beaker, add Tween-80, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 3000 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, emulsify for 20 minutes, and stand for 30 minutes after emulsification to obtain an emulsion; S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel. Set the temperature of the freeze dryer to -50°C and the vacuum degree to 0.1 mbar. Dry the pre-frozen gel at -50°C for 24 hours, and then heat it to 20°C at a rate of 1°C / min and dry it for 6 hours to obtain gel particles. S5: Mix beeswax and one quarter of the weight of MCT medium-chain triglycerides, heat in a water bath to 70°C to completely dissolve, and obtain a coating liquid. Preheat the gel particles prepared in step S3 to 40°C, and then add them to the coating liquid. After stirring for 1.5 minutes, separate the gel particles with a sieve, and immediately cool and solidify at 4°C to obtain a konjac hydrogel polymer.

[0024] Example 3: A highly absorbent konjac hydrogel polymer, comprising the following raw materials in parts by weight: 35 parts of acetylated konjac glucomannan, 12 parts of modified chitosan, 6 parts of calcium chloride solution, 2 parts of acetic acid solution, 4 parts of nanocellulose, 3 parts of beeswax, 12 parts of MCT medium chain triglycerides and 2 parts of emulsifier.

[0025] Preparation of acetylated konjac glucomannan: A1: Add konjac glucomannan to distilled water, stir and dissolve evenly to obtain 8wt% konjac glucomannan solution; cool 200mL konjac glucomannan solution to 4°C, then add sodium citrate to adjust the pH to 6.8, slowly add 3mL acetic anhydride dropwise under continuous stirring, stir and react for 2.5h, after the reaction is completed, add ethanol to terminate the reaction, centrifuge at 6000rpm for 10min, wash with distilled water until neutral, and vacuum dry at 55°C to constant weight to obtain acetylated konjac glucomannan; Preparation of modified chitosan: B1: Dissolve chitosan in 0.1M acetic acid aqueous solution, stir and dissolve evenly to obtain a chitosan solution with a concentration of 1.5wt%; dissolve 100mg of hexadecyltrimethylammonium bromide in 500mL of dimethyl sulfoxide solvent, heat to 50°C in a water bath, stir and dissolve evenly to obtain a hexadecyltrimethylammonium bromide solution; B2: Slowly drop 400 mL of the hexadecyltrimethylammonium bromide solution prepared in step B1 into 500 mL of the chitosan solution, heat to 55°C in a water bath, control the pH to 4.5, react for 3 hours, pour the reaction solution into 3000 mL of ethanol solution three times, centrifuge, filter, wash with ethanol three times, and vacuum dry at 60°C to constant weight to obtain modified chitosan; Preparation of Konjac Hydrogel Polymer: S1: dissolving acetylated konjac glucomannan in distilled water, stirring and dissolving uniformly, obtaining a 2wt% acetylated konjac glucomannan solution; dissolving modified chitosan in 0.15M acetic acid solution, stirring and dissolving uniformly, obtaining a chitosan solution; adding nanocellulose to distilled water, dispersing uniformly by ultrasonic treatment, obtaining a 1.5wt% nanocellulose suspension; S2: slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH to 6 during the process, stirring continuously for 50 min, adding the nanocellulose suspension prepared in step S1 in three batches, stirring continuously for 40 min, adding 0.4 M calcium chloride solution in four batches, stirring continuously for 50 min, to obtain a gel solution; S3: Add three quarters of MCT medium chain triglyceride by weight to a beaker, add glyceryl monostearate, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, set the speed to 2800 rpm, and slowly add the gel solution prepared in step S2 under continuous stirring, emulsify for 15 minutes, and stand for 30 minutes after emulsification to obtain an emulsion; S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel. Set the temperature of the freeze dryer to -50°C and the vacuum degree to 0.1 mbar. Dry the pre-frozen gel at -50°C for 24 hours, and then heat it to 20°C at a rate of 1°C / min and dry it for 6 hours to obtain gel particles. S5: Mix beeswax and one quarter of the weight of MCT medium-chain triglycerides, heat in a water bath to 70°C to completely dissolve, and obtain a coating liquid. Preheat the gel particles prepared in step S3 to 40°C, and then add them to the coating liquid. After stirring for 2 minutes, separate the gel particles with a sieve, and immediately cool and solidify at 4°C to obtain a konjac hydrogel polymer.

[0026] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that konjac glucomannan is used in Comparative Example 1 instead of acetylated konjac glucomannan.

[0027] Comparative Example 2: The operation of Comparative Example 2 is substantially the same as that of Example 2, except that chitosan is used in Comparative Example 2 instead of modified chitosan.

[0028] Comparative Example 3: The operation of Comparative Example 3 is basically the same as that of Example 2, except that nanocellulose is not used in Comparative Example 3.

[0029] Comparative Example 4: The operation of Comparative Example 4 is basically the same as that of Example 2, except that the interface induction method is not used in Comparative Example 4, and the gel solution is directly freeze-dried.

[0030] Performance Test: Water absorption test: 1 g of the konjac hydrogel polymer prepared in Example 2 and Comparative Examples 1 to 4 was placed in deionized water (control group), simulated gastric fluid (prepared with 0.2 w / v% NaCl solution and 0.7 w / v% HCl solution, pH 1.2, 37° C.) and simulated intestinal fluid (PBS buffer, pH 7.4, 37° C.), with an oscillation rate of 100 rpm to simulate the dynamic environment in the human stomach. Samples were taken out for measurement every 0.25 h, 0.5 h, 1 h, 2 h and 6 h, and the weight of the sample after water absorption was recorded, and then the sample was put back to continue soaking, and the water absorption ratio = (sample weight after water absorption - initial weight) / initial weight was calculated. The results of the deionized water test are as follows Figure 1 As shown; simulated gastric fluid test as Figure 2 As shown; simulated intestinal fluid test as Figure 3 shown.

[0031] Depend on Figure 1 , Figure 2 and Figure 3The results show that the konjac hydrogel polymer prepared by the present invention has a low water absorption rate in the initial stage, and the water absorption rate increases with time, which effectively avoids the discomfort reaction caused by excessive water absorption in the initial stage, while ensuring effective acid resistance and high water absorption; Figure 1 As a result, comparative example 1 has a faster initial water absorption rate, which may be due to the fact that the konjac glucomannan that has not been acetylated has a strong hydrophilicity; comparative example 2 has a higher initial water absorption rate, especially in the 1h to 2h stage, which may be due to the fact that the acetylated konjac glucomannan delays the initial water absorption rate, but due to the strong hydrophilicity of the unmodified chitosan, the water absorption rate gradually increases in the middle and late stages; the initial water absorption rate of comparative example 3 is similar to that of embodiment 2, but its total water absorption is significantly lower than that of embodiment 2, which may be due to the lack of high specific surface area and water absorption performance of nanocellulose, the water absorption speed is slow, the water absorption rate is low, and the physical reinforcement effect of nanocellulose is missing, and the structural stability is poor; the water absorption rate of comparative example 4 is unstable, which may be due to the lack of uniform pore structure generated by the interface induction method, the water absorption path is limited, and the water absorption rate and capacity are significantly affected.

[0032] Depend on Figure 2 As can be seen from the results, Comparative Example 1 initially exhibited a lower water absorption rate, and the water absorption rate was also significantly reduced. This may be due to the poor acid resistance of the unacetylated konjac glucomannan in an acidic environment and its easy degradation, which resulted in damage to the gel structure. The gel degradation limited the water absorption rate and may cause gel fragmentation, which in turn resulted in a significant decrease in water absorption capacity; Comparative Example 2 initially exhibited a lower water absorption rate, and the water absorption rate was significantly reduced after 2 hours. This may be due to the fact that the unmodified chitosan was easily soluble in an acidic environment, affecting the stability of the gel, and the gel structure was destroyed by the dissolution of chitosan, resulting in reduced water absorption capacity; Comparative Example 3 also initially exhibited an extremely low water absorption rate, and the water absorption rate was significantly reduced. This may be due to the lack of an unstable nanocellulose structure, the poor mechanical strength and toughness of the hydrogel during the water absorption process, and the loose overall structure; Comparative Example 4 initially absorbed water slowly, and the water absorption rate was low, which may be due to the lack of a pore structure generated by the interface induction method, and the poor structural stability.

[0033] Depend on Figure 3As can be seen from the results, Comparative Example 1 shows a faster initial water absorption rate, but the water absorption rate in the later stage decreases significantly. This may be due to the fact that the unacetylated konjac glucomannan has strong hydrophilicity and fast water absorption rate under a neutral environment, but too fast water absorption will cause excessive expansion of the gel, destroy the internal cross-linked network, cause structural damage and a decrease in water absorption capacity; Comparative Example 2 also shows a faster initial water absorption rate and a higher water absorption rate, which may be due to the strong hydrophilicity and fast water absorption rate of the unmodified chitosan; Comparative Example 3 shows a lower initial water absorption rate and a lower water absorption rate, which may be due to the lack of nanocellulose, insufficient mechanical strength and pore structure, which limits water penetration and limits the water absorption rate; Comparative Example 4 shows a slow water absorption rate, but a lower water absorption rate, which may be due to the lack of pore structure generated by the interface induction method, and the pore structure is not uniform enough, the water absorption path is limited, and the water absorption rate and capacity are affected.

[0034] Mechanical strength test: Use a universal material testing machine, set the compression mode, place the konjac hydrogel polymer samples prepared in Example 2 and Comparative Examples 1 to 3 in a compression fixture, gradually increase the pressure, and record the maximum compression force of the hydrogel before it breaks or deforms. The results are as follows: Figure 4 shown.

[0035] Depend on Figure 4 As a result, the konjac hydrogel polymer prepared by the present invention has excellent mechanical strength; Comparative Example 1 shows poor mechanical strength, which may be due to the high hydrophilicity of unmodified konjac glucomannan and the lack of structural stability brought by acetylation modification, and water molecules easily and quickly enter the interior of the gel, thereby causing the gel to be more easily deformed during compression; Comparative Example 2 shows poor mechanical strength, which may be due to the lack of hydrophobic interaction and molecular arrangement compactness brought by the long-chain modification of chitosan, resulting in the gel network structure showing poor stability during compression; Comparative Example 3 shows extremely poor mechanical strength, which may be due to the lack of nanocellulose, which greatly weakens the supporting structure of the hydrogel, lacks the physical reinforcement effect of nanocellulose, and the gel is more likely to break when compressed; Comparative Example 4 shows poor mechanical strength, which may be due to the lack of synergistic effect of the interface induction method, and the pore structure generated by the hydrogel after freeze drying is less and irregular, causing it to be more likely to break during compression.

[0036] Biocompatibility test: The konjac hydrogel polymer prepared in Examples 1 to 3 was placed in a sterile PBS buffer solution and extracted at 37°C for 24 hours. The extract was collected and sterilized by filtration with a 0.22 μm filter membrane. Human intestinal epithelial cells (Caco-2 cells) were inoculated into a 96-well plate, with 1×10 4Cells were placed in an incubator at 37°C and 5% CO2 for 24 hours, the culture medium was discarded, 100 μL of hydrogel extract was added and cultured for 24 hours. After the culture was completed, 20 μL of MTT reagent (concentration of 5 mg / mL) was added to each well, and the culture was continued for 4 hours. The culture medium was discarded and 150 μL of DMSO was added to dissolve the formazan crystals in the cells. The mixture was shaken for 5 minutes, and the absorbance value was measured at a wavelength of 570 nm using an ELISA reader. The cell survival rate was calculated as (absorbance of the experimental group - absorbance of the control group) × 100%. The control group was added with physiological saline. The results are shown in the figure. Figure 5 shown.

[0037] Depend on Figure 5 The results show that the konjac hydrogel polymer prepared by the present invention has excellent biocompatibility, will not cause adverse effects on the human body, and can be effectively used in food and pharmaceutical preparations.

[0038] Spectrum test: The SEM spectrum of the konjac hydrogel polymer sample prepared in Example 2 was tested using a scanning electron microscope. The results are as follows Figure 6 shown.

[0039] Depend on Figure 6 As a result, the present invention successfully and effectively prepared a konjac hydrogel polymer, which has an obvious porous structure and pore distribution in the image. A large number of evenly distributed pores are shown in the image to form a three-dimensional network structure. This porous property is consistent with the expected structure of a highly absorbent hydrogel. The pore wall structure is clear and thick, showing a supporting network, showing the result of the joint action of nanocellulose and a cross-linking agent (calcium ions). The entire image presents a porous network with good continuity, and the pores are interconnected, which conforms to the structural characteristics that should be present after the interface induction method and freeze-drying treatment.

[0040] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly water-absorbent konjac hydrogel polymer, It is characterized in that The composition comprises the following raw materials in parts by weight: 30-40 parts of acetylated konjac glucomannan, 10-15 parts of modified chitosan, 5-8 parts of calcium chloride solution, 1-3 parts of acetic acid solution, 3-5 parts of nanocellulose, 2-5 parts of beeswax, 10-15 parts of MCT medium chain triglyceride and 1-3 parts of emulsifier.

2. A highly water-absorbent konjac hydrogel polymer according to claim 1, It is characterized in that The emulsifier is any one of lecithin, Tween-80 and glyceryl monostearate.

3. A highly water-absorbent konjac hydrogel polymer according to claim 2, It is characterized in that The concentration of the calcium chloride solution is 0.2-0.5M; the concentration of the acetic acid solution is 0.1-0.2M.

4. A highly water-absorbent konjac hydrogel polymer according to claim 3, It is characterized in that The specific preparation steps of the acetylated konjac glucomannan are as follows: A1: adding konjac glucomannan to distilled water, stirring and dissolving uniformly to obtain a konjac glucomannan solution; cooling the konjac glucomannan solution, then adding sodium citrate to adjust the pH, slowly adding acetic anhydride dropwise under continuous stirring, stirring for reaction, and after the reaction is completed, adding ethanol to terminate the reaction, centrifuging, washing with distilled water until neutral, and vacuum drying to constant weight to obtain acetylated konjac glucomannan; In step A1, the amount of acetic anhydride used is 1-2% of the volume of the konjac glucomannan solution.

5. A highly water-absorbent konjac hydrogel polymer according to claim 4, It is characterized in that The specific preparation steps of the modified chitosan are as follows: B1: Dissolve chitosan in 0.1M acetic acid aqueous solution, stir and dissolve evenly to obtain a chitosan solution; dissolve hexadecyltrimethylammonium bromide in dimethyl sulfoxide solvent, heat in a water bath, stir and dissolve evenly to obtain a hexadecyltrimethylammonium bromide solution; B2: slowly drop the hexadecyltrimethylammonium bromide solution prepared in step B1 into the chitosan solution, heat in a water bath, control the pH, and after the reaction is completed, pour the reaction solution into an ethanol solution three times, centrifuge, filter, and wash with ethanol three times, and vacuum dry at 60°C to constant weight to obtain modified chitosan; In step B1, the ratio of the amount of hexadecyltrimethylammonium bromide to the dimethyl sulfoxide solution is 0.15-0.3 g:1 mL; In step B2, the volume ratio of the hexadecyltrimethylammonium bromide solution to the chitosan solution is 0.6 to 1:

1.

6. A method for preparing a highly water-absorbent konjac hydrogel polymer according to any one of claims 1 to 5, It is characterized in that The specific preparation steps are as follows: S1: dissolving acetylated konjac glucomannan in distilled water, stirring and dissolving uniformly to obtain an acetylated konjac glucomannan solution; dissolving modified chitosan in acetic acid solution, stirring and dissolving uniformly to obtain a chitosan solution; adding nanocellulose to distilled water, dispersing uniformly by ultrasonic treatment, and obtaining a nanocellulose suspension; S2: slowly adding the chitosan solution prepared in step S1 to the acetylated konjac glucomannan solution, controlling the pH during the process, stirring continuously, and after the reaction is completed, gradually adding the nanocellulose suspension prepared in step S1, stirring continuously, and after the reaction is completed, gradually adding the calcium chloride solution, stirring continuously, to obtain a gel solution; S3: Add three quarters of MCT medium chain triglyceride by weight to a beaker, add an emulsifier, stir and dissolve evenly to obtain an oil phase; place the oil phase under a homogenizer, and slowly add the gel solution prepared in step S2 under continuous stirring to emulsify the reaction, and let stand after the emulsification is completed to obtain an emulsion; S4: pre-freeze the emulsion prepared in step S3 at -20°C for 4 hours, and then pre-freeze at -80°C for 2 hours to obtain a pre-frozen gel, and freeze-dry the gel particles; S5: beeswax and one quarter of the weight of MCT medium chain triglyceride are mixed, and the mixture is completely dissolved by heating in a water bath to obtain a coating liquid. The gel particles prepared in step S3 are preheated and then added to the coating liquid. After stirring, the gel particles are separated by a sieve, and the mixture is immediately cooled and solidified to obtain a konjac hydrogel polymer.

7. A method for preparing a highly water-absorbent konjac hydrogel polymer according to claim 6, It is characterized in that In step S2, the nanocellulose suspension is added in three batches; and the calcium chloride solution is added in four batches.

8. A method for preparing a highly water-absorbent konjac hydrogel polymer according to claim 7, It is characterized in that The specific operation of the freeze-drying treatment in step S4 is as follows: set the temperature of the freeze dryer to -50°C and the vacuum degree to 0.1 mbar, dry the pre-frozen gel at -50°C for 24 hours, and then increase the temperature to 20°C at a rate of 1°C / min and dry for 6 hours.

Citation Information

Patent Citations

  • Method for preparing functional soluble and edible compound membranes

    CN105646951A

  • Preparation method for constructing composite hydrogel by compounding collagen base and nonionic polysaccharide

    CN106496608A

  • Preparation method of NCC / modified konjac glucomannan degradable film

    CN109776883A

  • Viscous composite hydrogel and preparation method and application thereof

    CN110437471A

  • High-water-absorption gel and preparation method thereof

    CN117229595A

Cited By

  • Preparation method of high-power water absorption konjac glucomannan

    CN121343020A